2012
DOI: 10.1016/j.jesp.2011.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Strangers in sync: Achieving embodied rapport through shared movements

Abstract: This paper examines the emergence of behavioral synchrony among strangers in the context of self-disclosure, and their path in predicting interaction quality. Specifically, we hypothesize that behavioral synchrony mediates the direct effect of self-disclosure on the development of embodied rapport. Same-sex stranger pairs (n=94) were randomly assigned to a videorecorded self-disclosure or control condition, and afterward each member rated their social interaction. Following the procedure used by Bernieri, Rezn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
160
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(169 citation statements)
references
References 26 publications
(25 reference statements)
6
160
0
3
Order By: Relevance
“…This is a strong indication of the relevance of these patterns of synchrony in the study of emotional interactions. Controlled laboratory studies have shown that mimicry and synchronization of behavior leads to prosocial behavior [20], increased cooperation [11,12], increased affiliation [21], and rapport [22]. The research summarized above leaves open two important questions, that we will examine in this paper: i) Does physiological synchrony develop in newly formed teams of unrelated participants in the absence of behavioral synchrony?…”
Section: Two Challenges Appear When Aiming To Measure and Analyze Teamentioning
confidence: 98%
“…This is a strong indication of the relevance of these patterns of synchrony in the study of emotional interactions. Controlled laboratory studies have shown that mimicry and synchronization of behavior leads to prosocial behavior [20], increased cooperation [11,12], increased affiliation [21], and rapport [22]. The research summarized above leaves open two important questions, that we will examine in this paper: i) Does physiological synchrony develop in newly formed teams of unrelated participants in the absence of behavioral synchrony?…”
Section: Two Challenges Appear When Aiming To Measure and Analyze Teamentioning
confidence: 98%
“…Rapport involves three dimensions: mutual attentiveness, positivity, and coordination. Scholars have recently argued that rapport also extends to physical sensations stemming from interpersonal coordination (Vacharkulksemsuk & Fredrickson, 2012). Given the association between interpersonal coordination and rapport (Bernieri & Rosenthal, 1991;Chartrand & Lakin, 2013), it is not surprising that interpersonal coordination has been linked to social support in prior research (Jones & Wirtz, 2007;Trees, 2000).…”
Section: Interpersonal Coordination and Language Style Matchingmentioning
confidence: 99%
“…Finally, it would be valuable to consider physical dimensions of rapport. Researchers have recently argued that rapport has a physiological component that is integrated with the perceptions of communicators and their shared movements (Vacharkulksemsuk & Fredrickson, 2012).…”
Section: Language Style Matching and Computer-mediated Supportmentioning
confidence: 99%
“…Indeed, much of the existing literature on synchrony and related phenomena underscores the bidirectional causal relationship between cohesiveness and coordination capability on the one hand, and sentiments associated with bonding on the other hand: synchrony can cause feelings of bonding and closeness (e.g., Hove & Risen, 2009;Valdesolo et al, 2010;Valdesolo & DeSteno, 2011;Vacharkulksemsuk & Fredrickson, 2012;Launay et al, 2013;Fischer et al, 2013;Fessler & Holbrook, 2014;Lumsden et al, 2014;Rabinowitch & Knafo-Noam, 2015;Tarr et al, 2015), and feelings of bonding and closeness can lead to synchrony (e.g., Lakin et al, 2003;Vacharkulksemsuk & Fredrickson, 2012;Cheung et al, 2015). Importantly, however, cohesiveness and coordination capability are logically distinct from feelings of bonding and closeness -although sentiments frequently undergird actions, they are not isomorphic with them.…”
mentioning
confidence: 99%